(untitled) (Global Journal of Human-Social Science, 2023)
This article is the result of a 20191 survey done in the capital of Mato Grosso do Sul with the participants of the 18th LGBT Citizenship Parade of Campo Grande The aim of the text is to discuss the issues of violence against the LGBTQIA population As a result of the reserach we have the centrality of sexuality as the main marker used to consider the situation of vulnerability of the LGBTQIA population that participated in the Parade In analytical terms at first we present statistical data that show how sexuality and violence go hand in hand with regard to the vulnerability experiences of Campo Grande s LGBTQIA population In a second moment from an intersectional and post-structuralist perspective we examine the social conditions that place LGBTQIA people in situations of inequality when compared to the heterosexual population